2013
DOI: 10.2105/ajph.2012.300976
|View full text |Cite
|
Sign up to set email alerts
|

Linking Sustainability Research to Intervention Types

Abstract: Researchers, funders, and managers of health programs and interventions have become concerned about their long-term sustainability. However, most research about sustainability has not considered the nature of the program to be sustained. Health-related interventions may differ in their likelihood of sustainability and in the factors likely to influence continuation. I suggest a framework for analyzing the sustainability of 6 types of interventions: (1) those implemented by individual providers; (2) programs re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
160
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(174 citation statements)
references
References 41 publications
(25 reference statements)
3
160
0
7
Order By: Relevance
“…Guidance by an explicit theoretical framework, adoption of clear working definitions, and use of adequate coherent-to-theory tools are pointed out as critical to further develop sustainability research and evaluation [13][14][15] . The choice for research strategy and the selection of factors to be investigated should be determined by the type of intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guidance by an explicit theoretical framework, adoption of clear working definitions, and use of adequate coherent-to-theory tools are pointed out as critical to further develop sustainability research and evaluation [13][14][15] . The choice for research strategy and the selection of factors to be investigated should be determined by the type of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The choice for research strategy and the selection of factors to be investigated should be determined by the type of intervention. Scheirer 15 proposes six different intervention types, including Interventions Requiring Coordination Among Multiple Staff. Aspects pertaining to the sustainability of this type of intervention comprise: administrative support; the role of program champions; culture and mission compatibility between the intervention and the organization; consonance of specific tasks related to the intervention with other organizational procedures; and continuity of financial resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practice-based approaches to research can align with traditional approaches (Green, 2006), and as demonstrated by the research questions posed here, may well serve to catalyze change. As practitioners strengthen efforts to promote sustainable change in communities (Scheirer, 2013), program and research goals will require increasing alignment. Cross-sector collaboration is also likely to strengthen this approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, few studies have explored the use of text-message based interventions to promote sexual health (Bobrow et al, 2014;Cornelius & St. Lawrence, 2009;Cole-Lewis & Kershaw, 2010;Reback, 2014 Scheirer (2013) posits that understanding technology alone is not sufficient for developing a sustainable health intervention. In light of the sensitive nature of sexual health information, we posit that perceived risk and privacy concerns will also be salient predictors of information technology adoption (Babel, 2012;Chiasson, Reddy, Kaplan, & Davidson, 2007;Schaupp, Carter, & McBride, 2010).…”
Section: Introductionmentioning
confidence: 99%